Analisis Jaringan Syaraf Tiruan Dengan Metode Backpropagation Dalam Jumlah Perkawinan Tidak Tercatat Di Siantar Utara - ,; ,; , (Seminar Nasional Informatika (SENATIKA), 2024)
Marriage is a permanent relationship between two people that is recognized as valid by the relevant society based on applicable marriage regulations. Marriage forms a family of the opposite sex with a husband and wife bond. In Indonesia, marriage is divided into two, namely registered marriage and unregistered marriage. In North Siantar District, it was found that 75,836 residents did not have a marriage certificate from the Pematang Siantar City Population and Civil Registration Service from 2017-2022. This data was obtained from the Population prediction is needed. Making a prediction requires a method that is appropriate to the problem that is occurring. Therefore, the appropriate method for making these predictions is the Artificial Neural Network method with the Backpropagation Algorithm. In this method, the number of years will be divided into 2 years, namely training and testing. Training data starts from 2017-2021 with a target in 2021, while testing data starts from 2018-2022 with a target in 2022. In this research the designed ANN architecture was obtained from the results of trial and error using the Matlab R2011A application. There are 5 architectural models chosen, namely 4-51-1,4-21-1,4-49-1,4-45-1-4-25-1. The 4-21-1 architecture model with a Mean Squred Error test of 0.000100326, on the 4-49-1 architecture produces a Mean Squred Error of 0.000189994, on the 4-45-1 architecture it produces a Mean Squred Error of 0.00009963, on the 4- 25-1 produces a Mean Squared Error of 0.00016365. Based on the best architecture produced in this research, namely the 4-51-1 architecture with 100% accuracy with a Mean Squared Error test of 0.000100326 at epoch 6352 Iterations which took 8 seconds to reach the goal.